Accessing learning resources described in semantically enriched weblogs. (18th July 2012) - Ruiz-Rube, I.; Cornejo, C.M.; Dodero, J.M.
In this paper, we describe how to design learning activities that dynamically provide thematic Web resources from a linked-data repository. The aim is to enable teachers to share a variable set of resources related to a given subject and postpone the actual resource delivery to the deployment or enactment of the course. We have proposed a Learning Activity Management System (LAMS) tool that provides an interface to automatically select the related resources to be delivered to the students who are running a learning activity. The thematic resource repository was a linked-data extension of the WordPress blog engine. This extension allows enriching text-based and video information contained in blog entries with RDF triples that can be externally managed and exploited. Our approach allows discovering learning resources from external linked data sets and enrich blog contents with linked-data, independently of the underlying conceptual model.